Crescimento e dinâmica reprodutiva do camarão-ferrinho Rimapenaeus constrictus (Stimpson, 1874) (Penaeoidea) no litoral norte do estado de São Paulo: síntese de cinco anos de estudo - Lopes, Ana Elisa Bielert [UNESP] (2017)
This is the first study to evaluate in broad spatiotemporal scales the growth parameters and population structure of Rimapenaeus constrictus, a barely damaged species composing the bycatch from shrimp fishing in the Western Atlantic. The abundance and size-class frequency distribution, growth, longevity and sex ratio were evaluated from monthly samples obtained in the northern littoral of São Paulo state from Jan/1998 to Jun/2003. We measured 5,812 individuals in which the sex ratio was skewed toward females; this was more evident in size classes greater than 10 mm in CL (carapace length) (binomial test, p<0.05). We selected 16 growth cohorts of females, and 8 of males, the majority consisting of younger individual cohorts excluded from the fisheries closure period. Growth estimates resulted in a CL∞ of 17.42 mm, a growth coefficient of 0.008 and a longevity of 579 days (1.60 year) for females, as well as a CL∞ of 16.3 mm, a growth coefficient of 0.01 and a longevity of 425 days (1.17 year) for males. Our results provide information of incontestable relevance to our knowledge of fishing management. We therefore strongly recommend that the fisheries closure period be changed to protect this species’ recruitment period and consequently its adult individuals. The reproduction and recruitment were analyzed in order to determine the size at the onset of sexual maturity, the reproductive and recruitment patterns and the copulation period. In our study, 6,456 shrimps were captured among which 5,774 were measured, which 4,322 were females and 1,452 were males. The estimated maturity was 8.3 mm and 11.2 mm, for males and females, respectively. Reproductive females were found over the 5-year study. These results suggests a continuous reproduction pattern, with peaks in summer and in spring. We verified a positive significant relation between reproductive females and temperature (lag +1 and +3), although the decrease in bottom water temperature in some peaks of reproductive activity (spawning), which was probably induced due to SACW intrusion. The recruitment was considered episodic and even though no significant relation was found between immatures and reproductive females, we suggested that the main recruitment peaks observed were a consequence of the major reproductive activities a few months prior to it. The copulation period was continuous in the sampled period, and ISP females (recently copulated) were significant correlated with reproductive males (lag 0). Thus, we propose that during this period the sexual proportion is 1:1, probably due to the migration of reproductive males, attracted to copulate. Our results provide information of incontestable relevance to our wide knowledge of the species’ reproductive biology, in order to support an accurate fishing management.